Determination of of Quantity of Materials in Suspensions and in Electrophoretic Coatings by UV-Visible Absorption Spectroscopy - Zaman, Ali Can; Kaya, Cengiz (ELECTROCHEMICAL SOC INC, 2015)
A spectroscopic technique is introduced to estimate the thickness and material quantity in coatings obtained by means of electrophoretic deposition (EPD). Stable polyvinylpyrrolidone (PVP) aided MWCNTs (Multi wall carbon nanotubes) suspensions were prepared by ultrasonication and centrifugation in isopropyl alcohol (IPA). Concentrations of PVP and MWCNTs in centrifuged suspensions were determined via UV-Visible absorption spectroscopy (UV-Vis) and thermogravimetric analysis (TG). Peak overlaps in UV-Vis spectrum of supernatants were eliminated by subtraction of MWCNTs' spectra. Concentration determination of PVP was enabled by using acquired spectrum after subtraction and calibration curve. Secondly, quantity of MWCNTs were determined by utilizing overlapped dilute suspensions while MWCNTs' concentration in one spectrum is known. Estimation of coating thickness and material quantity was done by evaluating UV-Vis spectra of dilute suspensions measured before and after EPD process. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: Electrochemistry; Materials Science